14C High Concentration Measurements with Relevance for Decommissioning of Nuclear Reactors. Issue 2 (2nd January 2019) - Enachescu, M; Stan-Sion, C
ABSTRACT: Decommissioning of nuclear reactors requires determination of all remnant long-lived isotopes that were produced during their long functioning time of the respective facilities. Radiocarbon ( 14 C) is such an isotope (T1/2 = 5730 yr), widely produced by neutron reactions in a thermal column of a nuclear reactor. Accelerator mass spectrometry (AMS) uses 14 C for precise dating of up to 50, 000 years old archaeological artifacts. This study presents a premier AMS measurement of high concentrated 14 C samples that are strictly forbidden in laboratories dedicated to perform 14 C dating. The determined 14 C activities range from the natural level (isotopic ratio 14 C/ 12 C = 1.2 × 10 –12 ) up to values of 10, 000 times higher. 14 C bulk and depth profile concentrations were measured in the thermal column disks of a decommissioned nuclear reactor. Results have shown that the 14 C concentration in the thermal column, close the reactor core is about 75 kBq/g and decreases to 0.7 Bq/g and the end of the column. Such AMS measurements are applicable for decommissioning and waste management of nuclear reactors.